Self-efficacy and Satisfaction With Teaching in Online Courses. Issue 6 (November 2020) - Hampton, Debra; Culp-Roche, Amanda; Hensley, Angie; Wilson, Jessica; Otts, Jo Ann; Thaxton-Wiggins, Amanda; Fruh, Sharon; Moser, Debra K.
Abstract : Background: Growth of online education has increased the demand for satisfied educators with perceived self-efficacy in online teaching. Teaching self-efficacy is an indicator of the belief that one can make a difference in student learning outcomes. Purpose: The aim of this study was to examine the level of teaching self-efficacy and satisfaction of online nursing faculty. Methods: This study used a descriptive cross-sectional survey design. Faculty satisfaction was measured by the Online Instructor Satisfaction Measure, and self-efficacy for online teaching was measured by the Michigan Nurse Educator's Sense of Efficacy for Online Teaching instrument. Results: The sample included 100 faculty in multiple schools of nursing who taught at least 1 online course in RN to BSN or graduate nursing programs. Overall, participants had relatively high levels of online teaching self-efficacy and satisfaction. Conclusions: Teacher self-efficacy can be facilitated through faculty development and increased experience teaching online.